The model approach to linking innovation announcements and market value of equity in service sector - Szutowski, Dawid; Szułczyńska, Julia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Despite the research conducted in this field of innovation the attempt to model the effects of communicating innovation through announcements on market value changes has not been undertaken yet. Thus the purpose of the present research was to model the relationship between communicating innovation and market value of service companies. Summary of the existing evidence relied on such methods of systematic literature studies as SALSA, one step forward and backward snowballing, meta-synthesis and mapping review procedure. In order to represent the relationship between innovation and market value in services a conceptual model is proposed. It encompasses seven innovation-level and seven firm-level predictors. It covers also interaction and second-order effects.The research was burdened with several limitations. Namely it was limited to papers published in English and included scientific articles and conference proceedings only. Further quantitative research aiming at testing the model empirically seems beneficial from the point of view of model development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 478, s. 425-435
Keywords: innovation; market value; service sector; service companies; innowacje; wartość rynkowa; sektor usługowy; przedsiębiorstwa usługowe